Early School Dropout and the Role of the Education Inspectorate in the Fight for Equality of Opportunity. The Catalan case - Alcalde Campos, Rosalina (Avances en Supervisión Educativa, 2025)
This article addresses the issue of early school dropout (AEP, by its Spanish acronym) as the result of accumulated inequalities, with a particular focus on the Catalan context.Its aim is to contribute to the reflection on the role that the Education Inspectorate can play in preventing AEP, beyond its regulatory function, especially in local contexts.To this end, it proposes an integrated reading of data, analysis and relevant practices. The article adopts a clearly propositive stance and is oriented towards strengthening local-level action through the collaboration between educational inspection services and municipal authorities. Strategic challenges and institutional guidelines are presented, emphasizing that addressing AEP requires a structural and nuanced approach, one that is committed to equity and grounded in a deep understanding of local dynamics.
Keywords: Early school dropout, educational equity, dropout prevention, secondary education, education inspectorate, local education policies, Catalonia